Prediction of Natural Frequency and Modes Shape of Wing Using Myklestad Method (Journal of University of Babylon for Engineering Sciences, 2018)
The paper studied and prediction the natural frequency and mod shapes for deflection, slop, shear and moment for four assumed cases for swept wing transport airplane with tow engine and different amount of fuel using Myklestad method which deal with transfer matrix technique for solving the mathematic modeling for these four cases. The maximum effect of the first mode deflection and slop on the tip of the wing (case one) and maximum effect of the second mode shear and moment on the mean root chord of the wing (case four) which were the most critical case.